Operationalizing protocol differences for EADC‐ADNI manual hippocampal segmentation. Issue 2 (23rd May 2013) - Boccardi, Marina; Bocchetta, Martina; Ganzola, Rossana; Robitaille, Nicolas; Redolfi, Alberto; Duchesne, Simon; Jack, Clifford R.; Frisoni, Giovanni B.; Bartzokis, George; Csernansky, John G.; de Leon, Mony J.; et al.
Abstract: Background: Hippocampal volumetry on magnetic resonance imaging is recognized as an Alzheimer's disease (AD) biomarker, and manual segmentation is the gold standard for measurement. However, a standard procedure is lacking. We operationalize and quantitate landmark differences to help a Delphi panel converge on a set of landmarks. Methods: One hundred percent of anatomic landmark variability across 12 different protocols for manual segmentation was reduced into four segmentation units (the minimum hippocampus, the alveus/fimbria, the tail, and the subiculum), which were segmented on magnetic resonance images by expert raters to estimate reliability and AD‐related atrophy. Results: Intra‐ and interrater reliability were more than 0.96 and 0.92, respectively, except for the alveus/fimbria, which were 0.86 and 0.77, respectively. Of all AD‐related atrophy, the minimum hippocampus contributed to 67%; tail, 24%; alveus/fimbria, 4%; and the subiculum, 5%. Conclusions: Anatomic landmark variability in available protocols can be reduced to four discrete and measurable segmentation units. Their quantitative assessment will help a Delphi panel to define a set of landmarks for a harmonized protocol.